(untitled) (Cambridge, U.K.,New York, 2000)
Few people would question nowadays that emotions influence beliefs but until recently little scientific research has been done on exactly how this effect takes place. This important new book, with contributions from some of the leading figures in the study of emotion, explores the relationship between emotions and beliefs from a number of different psychological perspectives. Combining theory with research, it seeks to develop coherent theoretical principles for understanding how emotions influence the content and strength of an individual's beliefs and their resistance or openness to modification. This book will prove an invaluable resource for all those interested in emotion.
Keywords: Emotions and cognition,Belief and doubt,Sự nhận thức và cảm xúc,Nghi ngờ và tin tưởng